Microstructures and electrochemical properties of Pt-doped amorphous V2O5 cathode films for thin film microbatteries - Kim, HK; Ok, YW; Seong, TY; Jeon, EJ; Cho, W; Yoon, YS (AMER INST PHYSICS, 2001)
We have investigated the effects of Pt doping on the structural and electrochemical properties of amorphous (a) V2O5 films grown by radio frequency magnetron sputtering. It is shown that the cycling performance of the alpha -V2O5 films is dependent upon the Pt content. Glancing angle x-ray diffraction and transmission electron microscopy examination shows that the undoped film is amorphous with some short-range order. However, doping of the films at a rf power of 10 W leads to a complete alpha -V2O5 film which shows the best cycling behavior among the samples. It is shown that the short-range ordered structure reappears when the films are doped by cosputtering at rf powers of 30 and 50 W. It is further shown that doping at a rf power of 50 W results in the formation of amorphous and nanocrystalline PtO5 phases embedded in the alpha -V2O5 matrix. (C) 2001 American Vacuum Society.
Keywords: LITHIUM SECONDARY BATTERIES; VANADIUM PENTOXIDE GELS; BEHAVIOR; INSERTION; ENERGY; CELLS